Influence of exercise training on e-NOS expression, nitric oxide production and mitochondrial function in the human placenta (2014)
Objective: To determine the effects of combined aerobic and resistance exercise training during the second half of pregnancy on endothelial NOS expression (eNOS), nitric oxide (NO) production and oxygen metabolism in human placenta.